2015
DOI: 10.1128/iai.02985-14
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6-Driven Inflammatory Response Induces Retinal Pathology in a Model of Ocular Toxoplasmosis Reactivation

Abstract: c Ocular inflammation is one of the consequences of infection with the protozoan parasite Toxoplasma gondii. Even if lesions are self-healing in immunocompetent persons, they pose a lifetime risk of reactivation and are a serious threat to vision. As there are virtually no immunological data on reactivating ocular toxoplasmosis, we established a model of direct intravitreal injection of parasites in previously infected mice with a homologous type II strain. Two different mouse strains with variable ability to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1
2

Year Published

2015
2015
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 28 publications
2
23
1
2
Order By: Relevance
“…cereus intraocular infection. On the other hand, another study reported a substantial role for IL-6 in the retinal inflammatory response in a mouse ocular toxoplasmosis reactivation model ( Rochet et al, 2015 ). In our study, IL-6 and other chemokines also increased during C .…”
Section: Discussionmentioning
confidence: 99%
“…cereus intraocular infection. On the other hand, another study reported a substantial role for IL-6 in the retinal inflammatory response in a mouse ocular toxoplasmosis reactivation model ( Rochet et al, 2015 ). In our study, IL-6 and other chemokines also increased during C .…”
Section: Discussionmentioning
confidence: 99%
“…A pathogenic role of Il6 is more recently highlighted by Levy and colleagues, who show that accumulation of the AMD biomarker apolipoprotein E (APOE) in subretinal macrophages up-regulates their expression of Il6, which in turn promotes their increased survival and induction of retinal pathology in light-damaged Cx3cr1−/− mice [ 59 ]. Additionally, a deleterious role of Il6 has been characterised in experimental ocular toxoplasmosis via antibody neutralisation, which considerably improved retinal morphology compared to controls [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Host-parasite relationships and coevolution have influenced the balance between the hosts and the parasite, susceptibility of the hosts, and virulence of the parasite [1,2]. Host species [8][9][10][11], breeds [12,13], strains [14][15][16][17], and families [18] display apparent differences in their susceptibility to the infection. The differences appear genetic [5,6] and may be explained by differences in the immune responses elicited [19,20].…”
Section: Introductionmentioning
confidence: 99%